Research advances in Zein-based nano-delivery systems - Liu, Xiaoxuan; Zhang, Minhong; Zhou, Xuelian; Wan, Mengjiao; Cui, Aiping; Xiao, Bang; Yang, Jianqiong; Liu, Hai (Frontiers in Nutrition, 2024)
Zein is the main vegetable protein from maize. In recent years, Zein has been widely used in pharmaceutical, agriculture, food, environmental protection and other fields because it has excellent biocompatibility and biosafety. However, there is still a lack of systematic review and research on Zein-based nano-delivery systems. This paper systematically reviews preparation and modification methods of Zein-based nanodelivery systems, based on the basic properties of Zein. It discusses the preparation of Zein nanoparticles and the influencing factors in detail, as well as analyzing the advantages and disadvantages of different preparation methods and summarizing modification methods of Zein nanoparticles. This study provides a new idea for the research of Zein-based nano-delivery system and promotes its application.